Added value of the pulmonary vein pulsatility index and its correlation to neonatal umbilical artery pH in fetal growth restrictions: a Vietnamese matched cohort study - Minh Son Pham; Dinh Vinh Tran; Chi Kong Pham; Thi Linh Giang Truong; Vu Quoc Huy Nguyen (BMC Pregnancy and Childbirth, 2023)
Abstract Background In clinical obstetrics, many guidelines recommended the use of Doppler fetal ductus venosus blood flow to monitor and to manage fetal growth restriction (FGR). The ductus venosus and the pulmonary venous flow pattern of fetuses are similar. Umbilical artery pH (UA pH) is essential in identifying adverse pregnancy outcomes, particularly in fetal growth restriction cases. Nevertheless, the literature indicates that the relationship between pulmonary vein pulsatility index (PVPI) and UA pH in FGR cases has not been well investigated. This study aimed to identify the alteration in PVPI in FGR cases and evaluate the correlation between PVPI and UA pH in FGR newborns. Methods This matched cohort study of singleton pregnancies from 28+ 0 to 40+ 0 weeks of gestation without congenital abnormalities included 135 cases of FGR (disease group) and 135 cases of normal growth (control group). The PVPI was measured at the proximal segment of the right or left pulmonary vein, approximately 5 mm from the left atrium wall. The umbilical artery pulsatility index (UAPI) was measured on the free umbilical cord. An elective cesarean section or labor induction are both options for ending the pregnancy, depending on the condition of the mother or fetus. Umbilical artery blood samples were collected within 5 min of delivery for UA pH measurement. SPSS version 20 and Medcalc version 20.1 were used for data analysis. Results FGR cases had a significantly higher mean fetal PVPI than the control group (1.16 ± 0.26 vs. 0.84 ± 0.16; p < 0.01), and PVPI and UAPI were positively correlated (r = 0.63; p < 0.001). PVPI and UA pH were negatively correlated in FGR patients, with r = -0.68; p < 0.001. The PVPI value on the 95th percentile had a prognostic value of UA pH < 7.20 with a sensitivity of 88.2%, specificity of 66.3%, positive predictive value of 46.9%, and negative predictive value of 94.3%. Conclusions There was a statistically significant difference in PVPI values in FGR cases compared to the normal growth group, a positive correlation between PVPI and UAPI, and a negative correlation between PVPI and UA pH. PVPI might have a prognostic meaning in predicting UA pH at birth.